Penerapan Metode Singular Spectrum Analysis dalam Peramalan Jumlah Produksi Beras di Kabupaten Gowa - Rezki Amalia Idrus; Ruliana Ruliana; Aswi Aswi (VARIANSI: Journal of Statistics and Its application on Teaching and Research, 2022)
Total rice production in Gowa Regency from January 2018 to December 2020 has decreased which is not significant every month, so it is necessary to do a forecast to anticipate food shortages in the future. This study aims to determine the yield of rice production in Gowa Regency and to model data from October 2021 to September 2022 using the Singular Spectrum Analysis (SSA) method. Based on the results of the analysis, the MAPE value obtained is 6.32% so it can be said that forecasting using the SSA method is very accurate